Telaah Kritis Eko-Teologi Gerakan Penyelamatan Lingkungan Komunitas Rumah Intaran Bali - Umi Ma'rifah; Grafis Skada; Muhammad Islahudin; Fauzan Hidayatullah; Luthfi Rahman; Tyas Tono Taufiq; Sukendar Sukendar; Sri Rejeki (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
This research describes a movement to save the environment called 'Gumuruh' or Movement Muncar Rumahku which is caused by destructive fishing such as illegal fishing which can cause environmental damage. This study also aims to find out what efforts have been made by Rumah Intraan in saving the environment. The research method used in this study is qualitative with a literature study approach. The results of this study are in the form of intaran houses which in their activities always use and utilize environmentally friendly materials both from the tools used in their daily life, food ingredients, and so on.